Pre-Islamic Poetry As A Hermeneutic Tool In Qur'anic Exegesis: The Questions Of Nafi Ibn Al-Azraq As A Model/ الشعر الجاهلي كأداة هرمينوطيقية في التفسير القرآني: مسائل نافع بن الأزرق أنموذجا - Mustafa Kadad; Mehmet Çetinkaya; Nesim Aytepe; Mehmet Ata Deniz (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This research addressing a central problematic in exegetical studies and philology: How did the literary heritage of a polytheistic milieu evolve into an indispensable hermeneutical tool for decoding the sacred monotheistic text? The study engages with this dialectical relationship, grounding its argument in the hypothesis that while Islam enacted a decisive doctrinal rupture with the Jahiliyyah, it did not institute a linguistic one; rather, it assimilated the prevailing linguistic system and semantically re-engineered it to serve the imperatives of Tawhid (monotheism). Employing a descriptive-analytical methodology, the paper examines applied models from Gharib al-Qur'an (obscure Quranic vocabulary), with a specific focus on the